Riviera's Golem, Haraway's cyborg: Reading Neuromancer as Baudrillard's simulation of crisis. - Davidson, Cynthia (Science Fiction Studies)
Cites the characters Riviera and Case in William Gibson's novel `Neuromancer' as examples of two creators contrasted by Jean Baudrillard in his essay `Simulacra and Simulacrum,' which focuses on the specular and discursive tradition of representation. Computer simulation of images; Description of the two characters; Movement from arresting to generative magic; Simulated death.